IL-6 and IL-10 are associated with good prognosis in early stage invasive breast cancer patients - Ahmad, Narmeen; Ammar, Aula; Storr, Sarah J.; Green, Andrew R.; Rakha, Emad; Ellis, Ian; Martin, Stewart G. (Springer, 2018)
Macrophage-associated cytokines play an important role in cancer metastasis however the functions of Interleukins (IL) 6 and 10 in breast cancer (BC) progression and metastasis are not clear. In this study the roles of IL-6/IL-10 in regulating vascular invasion and their prognostic significance in BC are investigated. MDA-MB-231 and MCF-7 migration (+/- IL-6 or IL-10) was assessed by scratch wound assay. Cancer cell adhesion to IL-6/IL-10 stimulated blood and lymphatic endothelial cells (EC) was investigated. Expression of IL-6 /IL-10 was assessed using immunohistochemistry in an annotated cohort of early stage BC (n=1380) and associations with clinicopathological variables and clinical outcome evaluated. IL-6 did not alter BC cell migration however a dose-dependent inhibition in MDA-MB-231 migration with IL-10 treatment was observed (P=0.03). BC cells were more adhesive to blood vs lymphatic EC however IL-6/IL-10 had no effect on adhesion patterns. High expression of IL-6/IL-10 was associated with clinicopathological criteria (e.g. hormone receptor status, all P<0.05), improved disease free survival (DFS; P<0.05) and improved BC specific survival (BCSS; only IL-6, P=0.017). However neither IL-6 nor IL-10 expression were independent prognostic factors from multivariate analysis. In BC subgroups, IL-6 and IL-10 were good prognosticators in terms of DFS in non-basal, non-triple negative (non-TN), ER-positive, PgR-positive (only IL-10), and Her-2-negative (only IL-6) BC (all P<0.05). IL-6 was associated with improved BCSS in non-basal, ER-positive and non-TN BC (all P<0.05).